Corelation Between Sum of Precordial ST Depression in Acute Inferior Myocardial Infarction with Stenosis Severity of Left Anterior Descending Artery - Karo, Kartika br; Ketaren, Andre Pasha; Hasan, Refli; Hasan, Harris; Mukhtar, Zulfikri; Lubis, Anggia Chairuddin (Talenta Publisher, 2019)
Background : There were many studies proved that precordial ST depression in Inferior STEMI show LAD disease from angiografi, but there were also many who unproved . Altought LAD disease was not the main cause of precordial ST depression in Inferior STEMI, but there were many patients with Inferior STEMI who had high grade LAD disease. Sum of precordial ST depression is one of ECG criteria that can help us to prove it . The aim of this study in to know if there is corelation between sum of precordial ST depression with LAD disease and the severity of LAD disease in Inferior STEMI patients with precordial ST depression . Methods : We analized 60 patients inferior STEMI with precordial ST depression onset less than 24 hours that hospitalized in Haji Adam Malik General Hospital since December 2013-June 2017. Patients were divided in to 4 groups based on sum of precordial ST depression. Bivariate analysis were made to see the corelation between sum of precordial ST depression with LAD disease and severity of LAD, p value < 0.05 is statistically significant. Result : Bivariate analysis show that there is strong corelation between sum of precordial ST depression with LAD disease (p=0.01). Sum of precordial ST depression also corelate with severity of LAD (p=0.01). There are also corelation with location of the lesion in proximal LAD and the complexity of the lesion but not statistically significant (p=0.233 and p=0.102). Analysis ROC curve sum of precordial ST depression to LAD disease give the cut off ≥5.15 mm with sensitivity 70% and spesificity 76.2%(AUC 0,752 ,95% CI: 0,620 – 0,883 p<0,001) Conclusion : There is strong corelation between sum of precordial ST depression with high grade LAD disease. The more the sum of precordial ST depression the more posibility high degree LAD disease ( p=0.01).